2019
DOI: 10.1101/565366
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The size of the immune repertoire of bacteria

Abstract: Some bacteria and archaea possess an immune system, based on the CRISPR-Cas mechanism, that confers adaptive immunity against phage. In such species, individual bacteria maintain a "cassette" of viral DNA elements called spacers as a memory of past infections. The typical cassette contains a few dozen spacers. Given that bacteria can have very large genomes, and since having more spacers should confer a better memory, it is puzzling that so little genetic space would be devoted by bacteria to their adaptive im… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 28 publications
(50 reference statements)
2
23
0
Order By: Relevance
“…It was discovered in bacteria as a naturally occurring phenomenon in their genome. Some bacteria survive viral attacks and develop resistance against any such future attack by copying part of the genetic sequence of the invading virus and storing it in the immune system [ 201 , 202 ]. This defense mechanism of the bacteria is expressed as clustered regularly interspaced short palindromic repeats, termed CRISPR.…”
Section: Isothermal Amplification Methods For the Detection Of Sars-cov-2 And Other Infectious Virusesmentioning
confidence: 99%
“…It was discovered in bacteria as a naturally occurring phenomenon in their genome. Some bacteria survive viral attacks and develop resistance against any such future attack by copying part of the genetic sequence of the invading virus and storing it in the immune system [ 201 , 202 ]. This defense mechanism of the bacteria is expressed as clustered regularly interspaced short palindromic repeats, termed CRISPR.…”
Section: Isothermal Amplification Methods For the Detection Of Sars-cov-2 And Other Infectious Virusesmentioning
confidence: 99%
“…Storing memory for molecular recognition is an efficient strategy for sensing and response to external stimuli. Apart from the cortical memory in the nervous system, molecular memory is also an integral part of the immune response, present in a broad range of organisms from the CRISPR-Cas system in bacteria [1][2][3] to adaptive immunity in vertebrates [4][5][6]. In all of these systems, a molecular encounter is encoded as a memory and is later retrieved and activated in response to a similar stimulus, be it a pathogenic reinfection or a re-exposure to a pheromone.…”
Section: Introductionmentioning
confidence: 99%
“…Memory recognition, however, is not limited to static patterns and can be desirable when classifying evolving stimuli that drive the system out of equilibrium. One such example is the adaptive immune system in which memory can effectively recognize evolved variants of previously encountered pathogens [4][5][6][7][8]. In a recent work, we have demonstrated that distributed learning strategies, which are desirable for pattern recognition in the stationary setup, can fail to reliably learn and classify dynamically evolving patterns [9].…”
Section: Introductionmentioning
confidence: 99%